Exposure to dust and bioaerosols at GB municipal waste handling sites - Keen, Christine; Sandys, Vince; Crook, Brian (New Zealand Journal of Health and Safety Practice, 2024)
Background Municipal waste in Britain contains organic matter. Handling this material can risk exposure to substances, including airborne dust and bioaerosol (airborne fungi, bacteria and their cellular components) that can impair human respiratory health. This paper combines the main findings of a series of studies conducted by the Health and Safety Executive in Great Britain to assess exposure to bioaerosols in various facilities processing municipal waste. Methods Site visits were conducted by a team of occupational hygienists and microbiologists. The key aims of the site visits were to quantify exposures to airborne dust and bioaerosol, to assess how waste processing methods and working practices contributed to worker exposure and to assess the effectiveness of exposure controls. Exposure measurement visits were conducted at materials recovery facilities (MRFs), waste transfer stations (WTS) and mechanical and biological treatment plants (MBTs). Findings High bioaerosol exposures, including endotoxin and Aspergillus fumigatus, both of which are associated with specific respiratory health conditions, were measured for several work activities. Higher risk tasks included work around unenclosed, high energy mechanical waste processing plant, cleaning operations using compressed air and high-pressure water jetting and hand sorting of waste at MRFs. Conclusions The higher exposures measured during this work could be reduced by increased sorting of waste at source to separate out food waste, a significant source of contamination in unsorted waste, improved plant design to provide greater containment of automated processes, targeted use of well-designed and suitably maintained LEV systems where practical and the adoption of low dust cleaning techniques.